Women’s career motivation: social barriers and enablers in Sudan - Mohamed, Souad; Abbashar, Aida; Abushama, Hala (Frontiers in Psychology, 2023)
This research makes an original and meaningful contribution by studying a previously neglected country in both the Middle East and Northeast Africa and women's career research. It identifies the challenges that have created barriers for Sudanese women's career progression, which has, in turn, limited their opportunities for career and leadership development. A critical literature review and analysis were carried out along with benchmarking success cases of countries with similar context. It has examined psychology and organizational behavior theories (self-efficacy theory, stereotype theory and implicit bias theory) and MENA examples of women's empowerment to conceptualize women's career motivations on global and regional scales. In addition, this study reports empirical findings of an extensive three-round Delphi study completed by 75 women leaders across sectors in Sudan. It was found that the roadblocks women face is broadly impacted by Sudan's unique social context, which influences and motivates women's careers in a variety of independent and intersecting ways. In addition, it provides policy recommendations for governments, workplaces, and other relevant stakeholders on how to best support women's career motivations and growth in Sudan through policy reforms and capacity development. This study provides the foundation for understanding and addressing challenges that women face in the workforce and the diversity of their experiences and needs as employees. Ultimately, this paper makes a significant contribution as it contextually identifies how and why an understanding of the barriers to Sudanese women's career motivations can support their advancement through historical, theoretical, and policymaking perspectives. Moreover, it is a starting point for creating gender-responsive policies in other similar countries within the MENA region and beyond.